Unveiling the Dynamics of Service Quality and Member Loyalty: A Comparative Analysis of Different Savings and Credit Cooperatives in Nepal - Sapkota, Keshab Prasad; Poudel Rai, Bimala; Bhattarai, Prakash C.; Devkota, Durga (Janapriya Journal of Interdisciplinary Studies, 2023)
This study explores the level of service quality and member satisfaction within the context of Savings and Credit Cooperatives (SACCOS) in Nepal. By using data from a survey of 1209 randomly selected SACCOS members, the study dealt with the demographic composition, service quality perceptions, and member satisfaction levels across three distinct SACCOS: Bindabasini-Kavrepalanchock, Mahila Milan-Makawanpur, and Siddhartha-Kapilbastu. The analysis uncovers intriguing patterns in demographic characteristics and establishes a positive correlation between service quality dimensions and both member loyalty and positive words of mouth. The findings highlight the crucial role of tailored service quality dimensions in fostering member loyalty, positive advocacy, and overall cooperative success. Findings of this study not only contributes to the understanding of cooperative management strategies but also provides insights for the enhancement of member experiences, leading to sustained growth and impact. Thus, the findings of this study have important implications for cooperatives, researchers, policy makers, cooperative movement, government for devising appropriate intervention to enhance members’ satisfaction levels.